2011
DOI: 10.1080/ac.66.5.2131080
|View full text |Cite
|
Sign up to set email alerts
|

Additive value of torsion to global longitudinal left ventricular strain in patients with reduced ejection fraction

Abstract: In patients with reduced LVEF, LVtor x LVE is a promising parameter that deserves research to establish its clinical meaning and prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
0
13
0
4
Order By: Relevance
“…There was no effect of the intervention on longitudinal strain, a consistent marker of subclinical cardiotoxicity [4], nor twist, which has also shown preliminary promise for prediction of cardiotoxicity [23,26,27]. Furthermore, in contrast to all previous observational studies of adults receiving anthracycline treatment [4,23], both parameters did not change over time.…”
Section: Discussionmentioning
confidence: 74%
“…There was no effect of the intervention on longitudinal strain, a consistent marker of subclinical cardiotoxicity [4], nor twist, which has also shown preliminary promise for prediction of cardiotoxicity [23,26,27]. Furthermore, in contrast to all previous observational studies of adults receiving anthracycline treatment [4,23], both parameters did not change over time.…”
Section: Discussionmentioning
confidence: 74%
“…Nine studies assessed the value of the relative change in GLS measured shortly after chemotherapy initiation compared with baseline (median [range] follow-up, 3 [2-6] months) . Most studies (7 of 9) used GE EchoPAC for GLS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…20,22,27 Relative Change in GLS During Treatment Nine studies assessed the value of the relative change in GLS measured shortly after chemotherapy initiation compared with baseline (median [range] follow-up, 3 [2-6] months). 11,12,20,21,23,25,26,28,32 Most studies (7 of 9) used GE EchoPAC for GLS analysis. Among studies treating GLS as a continuous variable, the summary OR for the unadjusted association with subsequent CTRCD per 1% relative decrease in GLS was 1.19 (95% CI, 1.01-1.39), 25,28,32 whereas one study reported a significant association after multivariable adjustment for age, traditional cardiovascular risk factors, and LVEF (eTable 3 in the Supplement).…”
Section: Absolute Change In Gls During Treatmentmentioning
confidence: 99%
See 2 more Smart Citations